HIGH-SKILLED TECHNOLOGY AND ENGINEERING PROFESSIONALS TRAINING AS A KEY FACTOR OF RUSSIAN FEDERATION SUCCESSFUL MODERNIZATION - E. V. Bodrova; A. R. Pirumov (Российский технологический журнал)
The article presents the analysis of domestic and foreign engineers training experience. Current problems the Russian Federation Higher Technical Education has faced are specialized as well as practical recommendations for engineering education quality improvement are proposed. It has been concluded that our country science and technology manpower regeneration should become one of the most important strategic directions amid the recovery from crisis, technological breakthrough and acceleration of modernization rate necessity. It is claimed that rather often technical university graduates lack in both knowledge of innovative technologies and adequate experience in research work. The authors consider that the main reasons of graduates low-level competency are the result of inadequate education requirements at school, lack of Higher education financing and specialist’s to bachelor’s programmes’ transformation.